COOPERATION OF KAZAKHSTAN AND CHINA WITHIN THE SILK ROAD ECONOMIC BELT - Daurenbekova Ayana, (Academic Journal of Physical and Chemical Sciences, 2020)
The purpose of the study is to identify the main problems and trends of cooperation between Kazakhstan and China in the light of the implementation of the Silk Road Economic Belt Strategy, which is one of the largest initiatives that form a new paradigm for the economic and overall geostrategic development of the world. To achieve this goal, the author identified the priorities and features of the participation of Kazakhstan and China in the formation and development of the Silk Road Economic Belt. In addition, the state of economic relations between China and Kazakhstan was analyzed in the following priority areas of cooperation: mutual trade, investment, and the scientific and technological sphere. The focus of the article is on the creation of transport corridors and transport and logistics centers within the Silk Road Economic Belt. In particular, the main directions of the development of transit potential in the Kazakh-Chinese direction are proposed. To strengthen mutual economic cooperation between Kazakhstan and China, the creation of the International Silk Road Financial Center in Kazakhstan with the definition of its functions has been proposed. The results of the study can be used by specialists of state bodies in the process of developing strategic program documents as part of the development of the Silk Road Economic Belt.